2017
DOI: 10.1111/jeb.13209
|View full text |Cite
|
Sign up to set email alerts
|

The divergence history of the perennial plant Linaria cavanillesii confirms a recent loss of self‐incompatibility

Abstract: Many angiosperms prevent inbreeding through a self-incompatibility (SI) system, but the loss of SI has been frequent in their evolutionary history. The loss of SI may often lead to an increase in the selfing rate, with the purging of inbreeding depression and the ultimate evolution of a selfing syndrome, where plants have smaller flowers with reduced pollen and nectar production. In this study, we used approximate Bayesian computation (ABC) to estimate the timing of divergence between populations of the plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 123 publications
(155 reference statements)
2
7
0
Order By: Relevance
“…This second possibility would be consistent with the observation that populations of L. cavanillesii are extremely isolated from one another, with F ST between 0.56 and 0.75 (Voillemot and Pannell ), implying that there has been no gene flow between the SC and SI population for a long time (Voillemot et al. ). Moreover, individuals in some of the SI populations of L. cavanillesii show incomplete self‐incompatibility (Voillemot and Pannell ), yet selfing appears not to have increased in frequency in these populations.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This second possibility would be consistent with the observation that populations of L. cavanillesii are extremely isolated from one another, with F ST between 0.56 and 0.75 (Voillemot and Pannell ), implying that there has been no gene flow between the SC and SI population for a long time (Voillemot et al. ). Moreover, individuals in some of the SI populations of L. cavanillesii show incomplete self‐incompatibility (Voillemot and Pannell ), yet selfing appears not to have increased in frequency in these populations.…”
Section: Discussionsupporting
confidence: 81%
“…; Voillemot et al. ), perhaps in response to selection for reproductive assurance or after a series of population bottlenecks that purged the population of its inbreeding depression (Kirkpatrick and Jarne ; Guo et al. ; Foxe et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By selfing, the incidence of deleterious alleles is expected to rise, but this can be overcome through DNA purging, for example due to bottlenecks after extreme environmental events (Cooper and Cooper 1995). Furthermore, plant phylogenies clearly showed that plants transitioned from self-incompatibility to self-compatibility multiple times, independently (Igic et al 2008;Goldberg et al 2010), and this is even confirmed by cases of recent acquisition of the selfing (Voillemot et al 2018). These aspects indicate the adaptive nature of the selfing trait, that could be advantageous at least in the short term (Cheptou 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It would be especially informative to compare estimates of outcrossing rates and inbreeding depression in the three known SC lineages ( T. barbata and T. coronopifolia with highly developed selfing syndromes and the undescribed species with slightly smaller floral parts) with SI plants (Crawford et al, 2008, 2019). Voillemot et al (2018) showed that a recent transition to SC in Linaria cavanillesii (Plantaginaceae) occurred without development of the selfing syndrome and that the population had a mixed mating system rather than being highly selfing. In addition, there was high inbreeding depression in an SI population, but it was not detectable in the aforementioned SC population (Voillemot and Pannell, 2017).…”
Section: Discussionmentioning
confidence: 99%